The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1177/0734242x211073852
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the effects of particle size pretreatment method on biogas yield of groundnut shells

Abstract: Optimising biogas yields from anaerobic digestion of organic wastes is significant to maximum energy recovery in the biodigestion process and has become an important topic of interest. Substrate particle size is an important process parameter in biogas production, and it precedes other pretreatments methods for the majority of the lignocellulose materials. Optimisation of biogas yield using Response Surface Methodology (RSM) was done, and temperature, hydraulic retention time and particle size were considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 51 publications
(86 reference statements)
2
12
0
Order By: Relevance
“… Jekayinfa et al (2020) reported 6 mm particle size as the optimum value for fresh biogas and methane yields of lignocellulose material. This result also supports what was reported by an earlier researcher when particle size was considered ( Olatunji et al, 2022b ). But this result contradicts what was recorded by Menardo et al (2012) that a particle size of 0.5 cm produced the optimum biogas and methane yields.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“… Jekayinfa et al (2020) reported 6 mm particle size as the optimum value for fresh biogas and methane yields of lignocellulose material. This result also supports what was reported by an earlier researcher when particle size was considered ( Olatunji et al, 2022b ). But this result contradicts what was recorded by Menardo et al (2012) that a particle size of 0.5 cm produced the optimum biogas and methane yields.…”
Section: Discussionsupporting
confidence: 93%
“…Economically, the technique requires further investigation at a commercial scale before it can be recommended. The detailed parameters related to particle sizes and Fe 3 O 4 additives show the influence of these operating parameters on the yield, as reported earlier ( Abdelsalam et al, 2016 ; Menardo et al, 2012 ; Olatunji et al, 2022b ). The results showed that combined particle size reduction with Fe 3 O 4 influences the biogas and methane yields more than the single pretreatment of Fe 3 O 4 nanoparticle additive.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The general low digestion efficiency of the lignocellulose feedstock, along with the longer retention time (30-40 days), results in limited efficiency [14]. The efficiency and proportion of the hydrolysis and morphological characteristics of lignocellulosic feedstocks can be adapted by biological, chemical, thermal, and mechanical pretreatment methods [15][16][17]. Combining two or more pretreatment techniques has been investigated, and different researchers have recommended its application [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The engineering use of the Arachis hypogea shells is limited due to their high lignocellulosic content [37]. The shells have been reported to consist of 37% cellulose, 18% hemicellulose, and 27% lignin [17]. Arachis hypogea shells' surface morphological examination is shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%